IF

5 - 4 = 23 8 - 1 = 63 6 - 16 = 32 9 - 9 = 78 3 - 9 = 6

Then

3 - 81 = ?

The answer is "0"

the logic is :

sq(5)-sqrt(4)=23

sq(8)-sqrt(1)=63

and so on ..........

sq(3)-sqrt(81)=0

ans=0; how? 5^2-sqrt4=23; 6^2-sqrt16=32; same 3^2-sqrt9=0..

A*A-SQUARE ROOT(B) 5-4=23 (ie) 25-2 8-1=63 (ie)64-1

like wise all so ans is 3-81=9-9=0

(5)^2 - (2)^(1/2) = 25-2=23 simillarly...... 3-81=(3)^2 - (81)^(1/2)=9-9=0

5² - √4 = 25 - 2 = 23 8² - √1 = 64 - 1 = 63 6² - √16 = 36 - 4 = 32 9² - √9 = 81 - 3 = 78 3² - √9 = 9 - 3 = 6

Therefore: 3² - √81 = 9 - 9 = 0

ans is 0 3-81=0. take a square of 3 & square root of 81.

ans=0 because square of ist no.,sqroot of 2nd no. is equal to given no.

Ans - 0 ( a - b ) = square of a- square root of b so 3 -81= 9-9= 0

hey dear friend i think answer will be (3*3=9)-root of 81=0.... so answer will be zero....

square of first - square root of second=0

If 5 - 4 = 23 8 - 1 = 63 6 -16 = 32 9 - 9 = 78 3 - 9 = 6 then 3 - 81 = ?

If 5-4=23, 6-16=32, 9-9=78, 3-9=6 then 3-61=??

3 2 = 7 5 4 = 23 9 9 = 78

3 81 = ??